2006
DOI: 10.1128/cvi.00158-06
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Malate Synthase- and MPT51-Based Serodiagnostic Assay as an Adjunct to Rapid Identification of Pulmonary Tuberculosis

Abstract: The 81-kDa malate synthase (MS; Rv 1837c) and the 27-kDa MPT51 (Rv 3803c) of Mycobacterium tuberculosis are immunodominant antigens recognized by serum antibodies from ϳ80% of human immunodeficiency virus-negative smear-positive tuberculosis patients from India. We now provide evidence that the use of the MS/MPT51-based serodiagnostic assay can serve as an adjunct to sputum microscopy in the rapid diagnosis of pulmonary tuberculosis.Approximately 50% of the pulmonary tuberculosis (PTB) cases in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
32
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 23 publications
(17 reference statements)
5
32
0
4
Order By: Relevance
“…The Mann-Whitney U test was used for two-group comparisons of median antibody reactivities. * , P Ͻ 0.05; ** , P Ͻ 0.01; *** , P Ͻ 0.001. ϩ /TB patients in the current cross-sectional study is similar to the combined sensitivity with both antigens in our earlier case-control study, 77 and 80%, respectively (1). The confirmation of the high sensitivity in the U.S., where TB can be diagnosed early due to the use of multiple technologies, and the high Ab responses in Indian HIV ϩ /TB patients together emphasize the value of these antigens in the rapid diagnosis of TB in countries where TB is rampant in HIV ϩ patients.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The Mann-Whitney U test was used for two-group comparisons of median antibody reactivities. * , P Ͻ 0.05; ** , P Ͻ 0.01; *** , P Ͻ 0.001. ϩ /TB patients in the current cross-sectional study is similar to the combined sensitivity with both antigens in our earlier case-control study, 77 and 80%, respectively (1). The confirmation of the high sensitivity in the U.S., where TB can be diagnosed early due to the use of multiple technologies, and the high Ab responses in Indian HIV ϩ /TB patients together emphasize the value of these antigens in the rapid diagnosis of TB in countries where TB is rampant in HIV ϩ patients.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, there was no difference of Ab responses to either antigen between asymptomatic U.S. controls and TST Ϫ and TST ϩ individuals from settings in which TB is endemic. As was observed in the prior U.S. case-control study, both HIV Ϫ /TB and HIV ϩ /TB patients had significantly higher Ab reactivities than subjects with LTBI, and U.S. HIV ϩ /TB demonstrated significantly higher reactivities irrespective of CD4 ϩ T-cell counts, viral loads, or sputum smear results compared to those of HIV Ϫ /TB patients (1,26,37). The evaluation of Ab reactivities in TB suspects with ORD revealed higher values in U.S. HIV ϩ /TB than U.S. HIV ϩ /ORD patients, while no such differences were observed among U.S. HIV Ϫ TB suspects.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Much progress has been made in the field of TB serology in the past decade (10,13,15; reviewed in reference 16), and recent studies have indicated that serodiagnosis in the form of detection of antibodies (Abs) to immunodominant antigens of Mycobacterium tuberculosis could be a useful adjunct test to diagnose TB earlier (2,3,17). Traditionally, serum is used to test for Abs to mycobacterial antigens.…”
mentioning
confidence: 99%